Analysis of taxation and government regulation of e-commerce - Makhmudov Lazizbek Ubaydullo ugli (THE INNOVATION ECONOMY, 2026)
this article analyzes the challenges and strategies for taxing and regulating e-commerce, with a focus on Uzbekistan’s context and global prac tices. It explores key issues such as defining the tax base, determining tax jurisdiction, and establishing effective tax collection mechanisms. The study high lights the complexities of taxing digital goods and services, cross-border transactions, and informal trade on social media platforms. Drawing on inter national experiences from the OECD, EU, USA, China, and CIS countries, the article proposes a hybrid tax ation model tailored to Uzbekistan’s economic and legal environment. This model emphasizes flexibil ity, fairness, systematic coverage, and digitalization, incorporating tools like automated identification platforms, unified tax reporting systems, and a mark ing system for e-commerce entities. Additionally, it suggests integrating an “e-commerce” function into card-to-card payment systems to enhance transpar ency and tax compliance. The proposed mechanisms aim to increase state revenue, strengthen regulatory oversight, reduce fraud, and align with international standards while fostering a competitive and equitable e-commerce ecosystem.